An Asymmetric Organocatalytic Aldol Reaction of a Hydrophobic Aldehyde in Aqueous Medium Running in Flow Mode - Schober, Lukas; Ratnam, Shahilan; Yamashita, Yasunobu; Adebar, Niklas; Pieper, Matthias; Berkessel, Albrecht; Hessel, Volker; Gröger, Harald (Synthesis, 2019)
Reaction conditions have been identified to conduct a one-pot asymmetric organocatalytic aldol reaction with a hydrophobic substrate in aqueous medium via a process running in flow mode. By employing a mixture of water and 2-propanol, a hydrophobic aldehyde and 3.6 mol% of an organocatalyst, this microreactor process affords the desired aldol adduct with a conversion of 74% and an enantioselectivity of 89% after a reaction time of 60 minutes.
Keywords: aldol reaction; asymmetric catalysis; continuously running processes; flow chemistry; organocatalysis; water